El discurso jurídico recontextualizado en la Facultad de Derecho de la Universidad Nacional de Rosario : análisis de dos materias de ciclo básico - Pezzetta, Silvina (2009)
" In this article, we aim to present some data obtained from classroom observations of two first-year courses taught at the Faculty of Law of the National University of Rosario. For these observations and their analysis, we have used as a guide the concepts of the sociology of education proposed by Basil Bernstein. Specifically, we are interested in the concepts of classification, framing, instructional discourse, regulative discourse, and pedagogical discourse. The theoretical framework of this work is the product of our ongoing doctoral research..."